Evaluating Environmental Weathering Effects on White Portland Cement using Hyperspectral Reflectance Analysis - I. Ahmed; U. K. Sharma; P. K. Garg; A. K. Thakur; Pritipadmaja (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Cement is a primary binding material that plays a crucial role in construction. This study used hyperspectral reflectance analysis to investigate the spectral reflectance characteristics of White Portland Cement (WPC) exposed to environmental conditions. The observation was made over a 150-day period. The reflectance of cement samples was measured using a spectroradiometer that captures the reflectance value of 994 discrete wavelength range from 339.3 nm to 2516.8 nm. These data were processed to calculate differential and double differential curves. Statistical techniques like moving average and smooth spline interpolation were employed to remove local fluctuations and observe the changing trends in reflectance over time. The study results provide insight into the temporal changes in the surface properties of WPC. The analysis also revealed significant changes in reflectance over time. The mean reflectance decreased from 90.397 on Day 0 to 83.092 on Day 150, showing surface degradation with time. However, the standard deviation of the reflectance increased initially from 7.318 on Day 0 to 7.766 on Day 30, then stabilized at 6.763 by Day 120. It was further increased to 7.496 by Day 150. The differential and double differential curves also show significant variations. The differential reflectance attained its maximum value of 0.199 on Day 60, and the double differential reflected maximum changes at 0.031 on Day 60. These results highlight the dynamic interaction between WPC surfaces and various environmental factors. The observed decrease in reflectance over time suggests surface ageing and potential material degradation, as reduced reflectance may indicate increased porosity or surface roughness due to environmental exposure. Overall, this study can offer a valuable tool for assessing cement-based materials' long-term durability and performance in the construction industry.